Realizing Promising Educational Practices in Academic Public Health: A Model for the Scholarship of Teaching and Learning - Neubauer, Leah C.; Merzel, Cheryl; Weist, Elizabeth M.; Corvin, Jaime Antoinette; Forsman, Allan; Fraser, Jacquie; Henderson, Heather L.; Hinyard, Leslie J.; Opacich, Karin Joann; Runnerstrom, Miryha G. (Frontiers in Public Health, 2022)
This paper presents a conceptual framework and critical considerations for the scholarship of teaching and learning (SoTL) in academic public health. Academic education for public health has undergone significant transformation over the last two decades; the demand for responsive and innovative public health pedagogy and training is immense. Sullivan and Galea (1) suggest that “public health educational programs must prepare graduates to engage with emerging public health issues with knowledge, skills, humility, and personal and professional confidence” and that schools, administrators, faculty, and educational staff play a role in developing best practices for teaching and learning in public health. The authors suggest that the path to developing promising practices (2,3) for teaching and learning in public health involves an articulated conceptual framework to guide the development and dissemination of scholarly, pedagogical innovations. Building on the philosophical foundations of SoTL, including Boyer (4), Shulman (5), and Brookfield (6), the authors conceptualize SoTL from the foundational belief that knowing and learning are communal tasks and that faculty are both scholars and learners in the practice of education. The paper advocates for SoTL as a form of engaged practice and scholarly inquiry that exists in contextually rich, diverse educational environments that abounds with uncertainty. SoTL is guided by an educational philosophy, values, and learning theories that envision educators critically examining themselves, their teaching practice, scholarly literature, and students’ learning to improve their teaching, enhance learning, and promote further inquiry. The authors suggest that SoTL involves the search for multiple forms of evidence and fosters dialogues on multiple interpretations and perspectives of the most promising practices of teaching and learning. The authors advocate for the term promising practices as an outcome of SoTL that supports and nurtures ongoing scientific discovery and knowledge generation, instead of supporting the search for best-ness in teaching and learning endeavors. SoTL should occur across formal, informal, and nonformal education environments, as well as advising and mentoring. A new conceptual model for Scholarly Teaching in Action and Practice (STAP) including key principles and implementation steps are detailed, along with practical challenges and considerations.